'Life then', 'life interrupted', 'life reclaimed': The fluctuation of agency in teenagers and young adults with cancer. (October 2018) - Davies, Jane; Kelly, Daniel; Hannigan, Ben
Abstract : Purpose: This paper presents findings from an in-depth study exploring agency in decision making when young people experience cancer. Methods: Exploratory case studies were utilised to examine all aspects of decision making, beginning with the onset of symptoms followed by diagnosis and treatment. Interviews, observations and documentary analysis were used to generate data. Multiple sources were selected to generate further insights and these included family, partners, friends and healthcare professionals who were close to the young people during their experience. Results: Three overarching themes were identified during analysis of the data: 'life then', 'life interrupted' and 'life reclaimed'. Key elements of these themes included a number of complex and interrelating factors which were interwoven within the everyday lives of the young people. In the 'life then' phase, 'holding on' to agency prior to diagnosis and the importance of close and intimate relationships was illuminated. In 'life interrupted', agentic power during treatment, in terms of the range of decision making and the complexity of the parental role, were prominent. In 'life reclaimed' the 'different but determined' nature of young people's behaviour and re-aligned agency was transparent as they were near to completing treatment. Conclusions: This study has culminated in the development of a model of individual cancer trajectories relating to the fluctuation of agency during young people's cancer experiences. These trajectories could be applied in future healthcare practice. Highlights: During the young person's cancer experience agency fluctuates over time. Personal, proxy and collective agency are evident the context of the experience. Three phases are identified, 'life then', 'life interrupted' and life reclaimed. Agency is important in decisions made in everyday life and not just in treatment.